Study of Growth and Production of Cotton Crops on Organic and Inorganic Fertilization - Diana, Nunik; Indratmi, Dian (Journal of Tropical Crop Science and Technology, 2022)
The study aimed to determine the effectiveness of organic and inorganic fertilization and to obtain the right dose of organic and inorganic fertilizers for the growth and production of seed cotton plants. The research was designed using a Randomized Group Design with 8 treatments repeated 5 times. The treatments were inorganic fertilizer Balittas package dose (100 kg N + 37.5 kg P2O5 + 37.5 kg K2O), Balittas package dose treatment with the addition of cottonseed cake bokashi, Balittas package dose with the addition of cow manure, Balittas package dose with the addition of cottonseed cake bokashi and cow manure and treatment with a dose of 1⁄2 Balittas package with the addition of organic fertilizers mentioned above, and treatment only with the use of organic fertilizers. The results showed that the treatment of organic and inorganic fertilizers was very effective in increasing the growth and production of cotton plants. The fertilization dose of Balittas package (100 kg N + 37.5 kg P2O5 + 37.5 kg K2O) + cottonseed cake bokashi + cow pukan gave better growth and production compared to other treatments, but the fertilization treatment of 1⁄2 dose of Balittas package (50 kg N + 18.75 kg P2O5 + 18.75 kg K2O) + cottonseed cake bokashi tended to be more efficient.